The Dynamics of Authoritative and Participative Leadership Communication in Shaping the Academic Careers of Islamic Higher Education Lecturers - Jamrizal Jamrizal; Nori Nopita Sari; Wahyu Iskandar; Abdul Wahid (AL-ISHLAH: Jurnal Pendidikan, 2025)
Leadership communication is a critical yet underexplored factor in shaping academic careers in Islamic higher education. This study investigates how authoritative and participative leadership communication influences lecturer development within Islamic universities in Jambi Province, Indonesia, amid increasing demands for professionalism and digital adaptation. Using a qualitative case study design, data were collected from 13 participants across three Islamic universities through semi-structured interviews, direct observations, and document analysis. Participants included lecturers and academic leaders, selected via purposive sampling. Data were analyzed thematically using Braun and Clarke’s six-phase framework to identify patterns of leadership behavior and communication strategies. Findings reveal that authoritative and participative communication modes function synergistically. Authoritative communication offers clarity, direction, and institutional alignment, while participative communication fosters collaboration, trust, and shared governance. Digital transformation enhances opportunities for participatory communication but also presents challenges such as uneven digital literacy. Communication practices grounded in Islamic ethical values—such as syura (consultation), amanah (trust), and musyawarah (deliberation)—strengthen moral integrity and organizational cohesion. Six dimensions of communication were identified as key drivers of lecturer career development: clarity of direction, transparency, mentoring, feedback, policy evaluation, and involvement in decision-making. An integrative communication model is proposed, showing that effective leadership in Islamic higher education is not only managerial but also ethical and developmental. The study underscores the need for leadership development programs that combine Islamic ethics with digital communication competence to enhance institutional resilience and lecturer empowerment.